Evaluation of miR-526b-3p, miR-1179, miR-3529-3p, miR-5011-5p as potential diagnostic biomarkers in isolated cervical dystonia - Gelisin, O.; Susgun, S.; Toruntay, C.; Yabaci, A.; Baran, G.; Gursoy, A. E. B.; Yildiz, G. B.; Yucesan, E. (MASSON EDITEUR, 2023)
Background. - Cervical dystonia (CD) also named spasmodic torticollis is the most common type of focal dystonias and characterized by abnormal head, neck, and shoulder movements due to invo-luntary muscular spasm. Although CD is mostly idiopathic, to date, several genes have been associated with CD. However, to the best of our knowledge, microRNAs (miRNAs) which are interacted with CD-associated genes have been not evaluated yet. miRNAs are regulatory small non-coding RNAs and are suggested as potential biomarkers for many diseases through their stability in clinical samples. Therefore, we aimed to assess the expression levels of miRNAs (miR-526b-3p, miR-1179, miR-3529-3p, miR-5011-5p) which are targeted the CD-associated genes, and evaluate their performance as diagnostic biomarkers. Methods. - Peripheral blood samples were obtained from 30 patients with isolated CD (ICD) and 25 healthy controls. The expression levels of miR-526b-3p, miR-1179, miR-3529-3p, and miR-5011-5p were analyzed via quantitative real-time PCR (qRT-PCR), and receiver operating characteristic (ROC) curves were generated to evaluate the diagnostic values. Results. - miR-526b-3p, miR-1179, and miR-3529-3p were significantly up-regulated while miR-5011-5p was significantly down-regulated in ICD patients compared to healthy controls. ROC analysis revealed that all miRNAs, especially miR-1179 and miR-3529-3p were statistically signifi-cant with the area under the curve (AUC) of 0.905 and 0.933, respectively. Conclusion. - Altered expression levels of aforementioned miRNAs may be associated with CD pathogenesis. Our findings suggest using these four miRNAs as remarkable biomarkers in the diagnosis of ICD. # 2023 Elsevier Masson SAS. All rights reserved.
Keywords: Cervical dystonia; miRNAs; ROC curve; AUC; Diagnostic biomarkers; EXPRESSION; SPECTRUM; GENETICS; Neurosciences & Neurology